Rehabilitasi Ekosistem Pesisir melalui Penanaman Mangrove di Terengganu, Malaysia: Indonesia - Hernawan, Budi; Dewi, Listiana Masyita; Anggitaratri, Zakia Novi; Fathin, Afif Naufal; Pranata, Nasywa Sekar Utami; Wafiq, Muhammad Azzim; Omar, Puteri Nur Atiqah Binti Omar; Muzaid, Intan Muzainah Binti Noorul (Jurnal Abdimas Madani dan Lestari (JAMALI), 2026)
Increasing coastal degradation in Terengganu, Malaysia, due to human activities and climate change, has prompted the need for ecosystem rehabilitation program through mangrove planting activities. This program is designed to restore coastal ecosystems, protect coastlines from erosion, and raise public awareness about the importance of the environment. Mangrove planting also provides economic benefits through ecotourism and sustainable fisheries. The implementation of activities involved students, lecturers, volunteers, and local communities in the MYCORAL 8.0 program, with stages of activities including site preparation, planting technique training, seedling planting, and initial monitoring. The results of the activity show an increase in mangrove coverage in the target area and the growth of active community participation in protecting the coastal environment. In addition to ecological benefits in the form of improved ecosystem quality and increased marine biota habitat, this activity also has a socio-economic impact through community empowerment and the potential for ecotourism development. These findings underscore the importance of integrating ecological, social, and technological aspects in coastal restoration, serving as a collaborative model that can be replicated in other regions. Overall, this program makes a tangible contribution to environmental conservation efforts while strengthening the relationship between academics and communities in addressing the challenges of climate change.